2015
DOI: 10.1080/00325481.2015.1033376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgen replacement therapy on cornea and tear function in men with idiopathic hypogonadotropic hypogonadism

Abstract: This is the first study that investigates the effects of ART on corneal structure and tear function in men. ART seems to have no short-term effects on corneal structure and tear function. Further publications of larger, long-term and controlled studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Contradicting findings have been reported for the association between IOP and testosterone in men. Intramuscular testosterone injections had no effect on the IOP in men with idiopathic hypogonadotropic hypogonadism [ 45 ], which is consistent with our results. However, in obese and overweight men IOP was found to be significantly correlated with testosterone levels [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…Contradicting findings have been reported for the association between IOP and testosterone in men. Intramuscular testosterone injections had no effect on the IOP in men with idiopathic hypogonadotropic hypogonadism [ 45 ], which is consistent with our results. However, in obese and overweight men IOP was found to be significantly correlated with testosterone levels [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…20 Systemic testosterone replacement therapy had no significant effect on IOP in men with idiopathic hypogonadotropic hypogonadism. 21 As this study was based on short-term treatment for 3 months, there was a limitation in determining the long-term effects of testosterone replacement therapy on IOP. However, a recently published observational study showed that IOP was significantly associated with testosterone, and the IOP in patients with testosterone above 3.0 ng/mL was significantly higher than that in patients with testosterone levels below 3.0 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines and as alluded to above, the topical use of 17-β-estradiol-3-phosphate drops did not significantly change Schirmer’s test scores in postmenopausal women [ 48 ]. In a study in men with idiopathic hypogonadotropic hypogonadism, androgen replacement therapy had little effect on the cornea and tear function [ 53 ].…”
Section: Methodsmentioning
confidence: 99%